A common backstop to the Single Resolution Fund. Issue 3 (3rd July 2019) - Brandt, Florian; Wohlfahrt, Matthias
Abstract : During the establishment of the Banking Union it has been agreed to develop a common backstop to the Single Resolution Fund. The following key principles constitute the point of departure of this paper: 1. Fiscal neutrality in the medium term; 2. Instrument of last resort; 3. Equivalent treatment across all Member States in the Banking Union; and 4. No costs for non-Banking Union Member States. For each aspect the legal and regulatory background as well as the economic implications are provided. They significantly influence the common backstop's final design and the choice of an adequate provider for the steady state.